Russia and Ukraine : entangled histories, diverging states - Popova, Maria; Shevel, Oxana (Polity Press, 2024)
"In February 2022, Russian missiles rained on Ukrainian cities and tanks rolled towards Kyiv to end Ukrainian independent statehood. President Zelensky declined a western evacuation offer and rallied the army and citizens to defend Ukraine. What are the roots of this war which has devastated Ukraine, upended the international legal order, and brought back the spectre of nuclear escalation? How is it that these supposedly "brotherly peoples" became each other's worst nightmare? In Russia and Ukraine: Entangled Histories, Divergent States , Maria Popova and Oxana Shevel explain how over the last thirty years Russia and Ukraine diverged politically ending up on a catastrophic collision course. Russia slid back into authoritarianism and imperialism, while Ukraine consolidated a competitive political system and pro-European identity. As Ukraine built a democratic nation-state, Russia refused to accept it and came to see it as an "anti-Russia" project. After political pressure and economic levers proved ineffective and even counterproductive, Putin went to war to force Ukraine back into the fold of the "Russian world." Ukraine resisted, determined to pursue European integration as a sovereign state. These irreconcilable goals, rather than geopolitical wrangling between Russia and the West over NATO expansion, are - the authors argue - essential to understanding Russia's war on Ukraine."--
Keywords: kansainväliset suhteet; Venäjän hyökkäys Ukrainaan 2022; Ukraina; Venäjä